2020
DOI: 10.48550/arxiv.2009.00967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Big Ramsey degrees using parameter spaces

Abstract: We show that the universal homogeneous partial order has finite big Ramsey degrees and discuss several corollaries. Our proof uses parameter spaces and the Carlson-Simpson theorem rather than (a strengthening of) the Halpern-Läuchli theorem and the Milliken tree theorem, which are the primary tools used to give bounds on big Ramsey degrees elsewhere (originating from work of Laver and Milliken). This new technique has many additional applications. To demonstrate this, we show that the homogeneous universal tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…We refer to the paper [10] for comprehensive background on historical and recent results on big Ramsey degrees. This paper extends and concludes work in [8], [9], [11], [12], [13], [14], [17], [18], [25], [28], and [32] for free amalgamation classes with relations of arity at most two and finitely many forbidden irreducible substructures.…”
Section: Introductionsupporting
confidence: 76%
“…We refer to the paper [10] for comprehensive background on historical and recent results on big Ramsey degrees. This paper extends and concludes work in [8], [9], [11], [12], [13], [14], [17], [18], [25], [28], and [32] for free amalgamation classes with relations of arity at most two and finitely many forbidden irreducible substructures.…”
Section: Introductionsupporting
confidence: 76%
“…Hubička recently developed a new method to handle forbidden substructures utilizing topological Ramsey spaces of parameter words due to Carlson and Simpson [7]. In [39], he applied his method to prove that the homogeneous partial order and Urysohn S-metric spaces (where S is a set of non-negative reals with 0 ∈ S satisfying the 4-values condition) have finite big Ramsey degrees. He also showed that this method is quite broad and can be applied to yield a short proof of finite big Ramsey degrees in G 3 .…”
Section: Historical Highlights Recent Results and Methodsmentioning
confidence: 99%
“…He also showed that this method is quite broad and can be applied to yield a short proof of finite big Ramsey degrees in G 3 . Beginning with the upper bounds in [39], the exact big Ramsey degrees of the generic partial order have been characterized in [2] by Balko, Chodounský, Hubička, Konečný, Vena, Zucker, and the author. Also utilizing techniques from [39], Balko, Chodounský, Hubička, Konečný, Nešetřil, and Vena in [4] have found a condition which guarantees finite big Ramsey degrees for binary relational homogeneous structures with strong amalgamation.…”
Section: Historical Highlights Recent Results and Methodsmentioning
confidence: 99%
See 2 more Smart Citations